Exploring the associations between health confidence, self-efficacy, health activation and healthy behaviours in primary school children - Lixia Ge; Joseph Antonio De Castro Molina; Hui Ting Foo; Rochelle Chua; Chin Fung Ong (Discover Public Health)
Abstract Background Promoting healthy behaviours is crucial for improving health outcomes. However, empirical research on the interplay between self-efficacy and health activation in primary school children is limited. This study investigated their association to inform strategies for health educators, healthcare providers, researchers, and policymakers in developing tailored interventions for this population. Methods A cross-sectional survey with 597 children from four primary schools was conducted. Health confidence, self-efficacy, and health activation were measured using the Health Confidence Scale (HCS), the Healthy Eating and Physical Activity Self-Efficacy Questionnaire for Children (HEPASEQ-C), and the Health Activation Scale for Children (HAS-C), respectively. Healthy behaviours, including vegetable and fruit consumption and physical activity, were collected as dependent variables. Multiple logistic regression models and mediation analyses were employed to examine the associations. Results Participants were aged between 8 and 12 years, with 50.1% being boys and 64.8% of Chinese ethnicity. Higher levels of health confidence, self-efficacy and health activation were independently associated with vegetables and fruits consumption and physical activity. The associations of self-efficacy with both vegetable consumption and physical activity were mediated by health activation, with indirect effect coefficients of 0.33 and 0.23, respectively (both p < 0.05). Conclusion The findings underscore the importance of self-efficacy and health activation in promoting healthy behaviours. Health activation mediated the relationship between self-efficacy and healthy behaviours, highlighting the need to target these psychological determinants, particularly health activation, in interventions aimed at fostering healthy behaviours among children.